Poetry of Maledictions: A Commentary on the Ibis of Ovid - Gordon, Carol Jean (My University, 1992)
The Ibis of Ovid, an enigmatic poem written during the poet's exile at Tomis, contains a series of violent and allusive imprecations drawn from history and mythology. The purpose of this dissertation is to provide a detailed study of the poem, to aid readers in their understanding and appreciation of the historiae caecae and ambages in which Ovid takes such delight; accordingly, an introductory chapter attempts to outline the historical and literary background to the poem, with particular attention devoted to placing the poem more firmly within the sphere of imprecatory writing in the ancient world. Following this is an explanatory commentary which covers models, parallels for topoi, and explanations of references, meanings, and allusions in the Ibis. Inevitably, this commentary is indebted to the efforts of previous commentators; however, I have endeavor throughout to suggest additional lines of inquiry and to provide a fresh perspective on a challenging work.
Keywords: Ibis; Ovid